Evaluation of possible mechanisms of three plants for blood glucose control in diabetes - Dalu, Damayanthi; Dhulipala, Satyavati (Bangladesh Journal of Pharmacology, 2016)
This study was conducted to provide the evidence for the mechanism of anti-diabetic activity of Cocculus orbiculatus, Leea indica and Ventilago maderaspatana. This was accomplished by employing methods like uptake of glucose, glycogen synthesis and inhibition of ?-glucosidase. For uptake of glucose, diaphragms were dissected out in Tyrode solution with 2% glucose and assayed for glucose content. In glycogen synthesis methodology liver, skeletal muscle and cardiac muscles were isolated, homogenized and glycogen content was analyzed. In ?-glucosidase enzyme inhibition procedure involved estimation of ?-glucosidase enzyme inhibition. All the three plant extracts exhibited significant (p<0.05 - p<0.01) anti-diabetic activity by increasing glucose uptake, glycogen synthesis and inhibiting ?-glucosidase enzyme. Among the three plants, V. maderaspatana (500 mg/kg) exhibited higher glucose uptake, glycogen content and ?-glucosidase inhibition activity (IC50 145 µg/mL). The present experimental results evidenced the anti-diabetic activity of three plants by all the three mechanisms.